FINO A CHE PUNTO È SOSTENIBILE IL CONSUMO DI SUOLO? - Federico Martellozzo; Federico Amato; Beniamino Murgante (Bollettino della Società Geografica Italiana, 2019)
It is well known that human activities are among the major causes for global environmental change. In particular, the developments of rural and natural land, together with the swelling of natu-ral resources from urban population, exacerbate this environmental burden. The aims of this research are threefold: at first it wants to produce cartographical estimating potential future urbanization and land cover changes (LUCC) in Italy according to different and contrasting policy-oriented scenarios; secondly, by comparing observed and projected results, it aims to un-derline how landscape planning in Italy often favoured economic returns neglecting to consider sustainability drawbacks; third, this work wants to trigger the debate regarding the need to reca-librate regional planning priorities in order to achieve sustainability targets. This study couples spatial cellular automata modelling with spatial multi criteria analysis, and is the first attempt (to our best knowledge) to map and estimate possible consequences of future urban growth and LUCC under different scenarios for the whole Italy at once. It features the combination of loco-regional and national criteria, thus enabling – by comparison – the understanding of their relative importance in influencing LUCC for the future, and building on findings that are relevant at the local scale while drawing a larger picture at the national scale. We believe this a useful tool to help in elaborating national and local land development pathways for the future.